"Un tal Scorza empieza a meterse en camisa de once varas": The ambiguous position of the narrator in La guerra silenciosa - Polo Taboada, Marco (2019)
Based on Antonio Cornejo Polar’s approach to the migrant subject and discourse, this paper analyzes the instability of the narrator of Redoble por Rancas and the author's self-portrayal in La tumba del relámpago, the first and last novels of the series “The Silent War”, by the Peruvian author Manuel Scorza. Scrutiny of both narrative strategies will demonstrate the inoperability of the habitual categories through which the five-novel series has been interpreted, and the complex multiple discursive framework through which the author strives to narrow the distance between the reality described and its textual representation.